Kajian Pemikiran Islam Tentang Sertifikasi Pendidik dalam Meningkatkan Kompetensi Guru Perspektif UU. No 14 Tahun 2005 - Andre Surya Wijaya, Andre (Edukais : Jurnal Pemikiran Keislaman, 2024)
This research aims to analyze educator certification in the perspective of Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers, as well as examining the concept of teacher competency according to Imam Al-Ghazali in the book Ayyuhal Walad And Bidayah al-Hidayah. This research is motivated by the importance of harmony between formal national education standards and the ethical values ​​of classical Islamic scholarship. The method used is library research with a qualitative approach. Primary data sources come from the classic book by Al-Ghazali and legal and regulatory documents, while data analysis techniques use grounded theory, ethnography and ethnomethodology methods. The research results show that teacher competence according to Al-Ghazali includes three main aspects, namely pedagogical competence, personality competence and social competence. All three emphasize the importance of sincerity, example and moral responsibility in educating. Meanwhile, Law no. 14 of 2005 states that a professional educator must meet academic qualifications, have educator certification, and be physically and mentally healthy. These two perspectives have common ground in terms of the importance of integrity, intellectual capacity, and dedication to the formation of students' character. In conclusion, this research makes an important contribution in harmonizing the classical Islamic scientific paradigm and national education policy, as well as encouraging teachers to continue to improve their professional competence and qualifications. The implication of this research is the need to strengthen teacher training which is not only based on regulations, but is also filled with spiritual and ethical values ​​in the Islamic education tradition.